2013
DOI: 10.1111/jfd.12080
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of temperature and crowding trigger acute viral nervous necrosis in zebra fish, Brachydanio rerio (Hamilton‐Buchanan), subclinically infected with betanodavirus

Abstract: Short CommunicationElevation of temperature and crowding trigger acute viral nervous necrosis in zebra fish, Brachydanio rerio (Hamilton-Buchanan), subclinically infected with betanodavirus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…; Chou et al . ; Small & Bilodeau ; Binesh ). In our experimental condition, olive flounder injected with an infective agent (FLIV) were placed in a condition with water temperature shifting or different stocking densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chou et al . ; Small & Bilodeau ; Binesh ). In our experimental condition, olive flounder injected with an infective agent (FLIV) were placed in a condition with water temperature shifting or different stocking densities.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of stressors such as water temperature and high stock density leads to high mortality in fish (Barton & Schreck 1987;Tagawa et al 2004). Furthermore, stress enhances pathogen susceptibility and mortality in fish (Chou, Li & Lo 1994;Chou et al 1998;Chou et al 1999;Small & Bilodeau 2005;Binesh 2014). In our experimental condition, olive flounder injected with an infective agent (FLIV) were placed in a condition with water temperature shifting or different stocking densities.…”
Section: Discussionmentioning
confidence: 99%
“…The association of disease outbreaks with seasonality (May to October, when the water has relatively high temperatures) further indicates the involvement of an infectious agent, since water temperature affects the emergence of a wide range of parasitic, bacterial, and viral diseases of fish (14,(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Examples for the influence of the environmental conditions on disease progression (33) include piscine rhabdoviruses, in which classical acute hemorrhagic septicemias (35,36) may change to subacute, chronic, or nervous forms (9,(37)(38)(39)(40)(41), and these are seldom difficult to visualize and monitor in open waters (42). Likewise, the influence of harsh husbandry conditions in close community on the severity of the disease was documented for VNN (14,43).…”
Section: Discussionmentioning
confidence: 99%
“…Hodneland, Garca, Balbuena, Zarza, and Fouz (2011) According to this, we should have expected to see higher levels of mortality in the present study, with the measured mean brain Ct values of 13.12 and 9.92 for IM-and immersion-infected fish, respectively. Although there are indications that an active infection was present, with replicating virus in infected brains (e.g., the number of infective particles increased between 7 and 15 dpi from 10 6.83 to 10 9.63 TCID 50 /ml in the immersion-infected fish), we postulate that the fish from both infection groups were sub-clinically infected with the virus, resulting in the absence of clinical signs of the disease with only low levels of mortality resulting (Binesh, 2014). This is supported by the fact that Hodneland et al (2011) observed survivors from a prior VER outbreak, with brain Ct values of 11.6-31.0, dying only when water temperatures increased, a known trigger for VER outbreaks, indicating their carrier status for Betanodavirus.…”
Section: Discussionmentioning
confidence: 93%